Formulation Development And Evaluation Of Azilsartan Medoxomil Sustained Release Tablet - Aayushi Sharma; Jeevan Patel; Shabnam Khan; Shivani Khoware; Shweta Shrivas; Rakesh Patel; Ramakant Sharma (International Journal of Pharmacy and Analytical Research, 2024)
The purpose of the study was To design, formulate and evaluate sustained release tablets of Azilsartan Medoxomil which is expected to deliver the drug in controlled and sustained release manner with reduce frequency of drug administration, reduce GI tract side effects and improve patient compliance. The present work is aimed at preparation and evaluation of Sustained Release matrix tablets of Azilsartan Medoxomil using using HPMC, Vinyl pyrrolidone vinyl acetate as polymers in varying ratios. The tablet were evaluated for its Thickness, Hardness, Friability, Friability, Disintegration and in vitro drug release studies. The FTIR studies revealed no chemical interaction between the drug molecule and polymers and found that drug was compatible with used polymer. In vitro drug release study confirms that formulation F4 was the best formulation as it releases 98.87 % at the end of 12 hr. This confirms the developed Azilsartan Medoxomil tablet are promising for sustained release drug delivery system.